Quantitative analysis of internal wave detection variability in the Northern Gulf of California using Synthetic Aperture Radar - Diego Gámez; Bernardo Shirasago; Edgar Pérez (Tecnología y ciencias del agua, 2018)
Gámez, D., Shirasago, D., & Pérez, E. (January-February, 2018). Quantitative analysis of internal wave detection variability in the Northern Gulf of California using Synthetic Aperture Radar. Water Technology and Sciences (in Spanish), 9(1), 125-133, DOI: 10.24850/j-tyca-2018-01-09.